Răspuns :
(a+b):2= 7,8 => a+b= 7,8 x 2= 15,6
(a+b+c):3=7,3
(15,6+c):3=7,3
15,6+c= 7,3 x 3
15,6+c= 21,9
c= 21,9-15,6
c= 6,3
(a+b+c):3=7,3
(15,6+c):3=7,3
15,6+c= 7,3 x 3
15,6+c= 21,9
c= 21,9-15,6
c= 6,3
Ma = ( a + b ) : 2 = 7,8
a + b = 2 × 7,8 = 15,6 → suma primelor doua numere
Ma = ( a + b + c ) : 3 = 7,3
a + b + c = 3 × 7,3 = 21,9 → suma celor 3 numere
a + b + c = 21,9
a + b = 15,6
_____________
15,6 + c = 21,9
c = 21,9 - 15,6
c = 6,3
a + b = 2 × 7,8 = 15,6 → suma primelor doua numere
Ma = ( a + b + c ) : 3 = 7,3
a + b + c = 3 × 7,3 = 21,9 → suma celor 3 numere
a + b + c = 21,9
a + b = 15,6
_____________
15,6 + c = 21,9
c = 21,9 - 15,6
c = 6,3